P008 A systematic review and meta-analysis of inflammatory bowel disease activity and sleep quality. (7th October 2021) - Barnes, A; Spizzo, P; Mountifield, R; Bampton, P; Andrews, J; Fraser, R; Mukherjee, S
Abstract: Background: Poor sleep quality has been associated with active inflammatory bowel disease (IBD) in several studies. This review examines sleep quality in people with active IBD and in those in remission, with meta-analyses performed, considering subjective and objective sleep quality and IBD activity. Methods: Electronic databases were searched from inception to December 1st 2020. A random effects model was used with separate meta-analyses performed for objective and subjective sleep and IBD activity, considering sleep quality in active and inactive IBD. Results: 19 studies were included in the qualitative review representing 4972 IBD patients. Subjective IBD activity (11 studies) was associated with subjective sleep quality with pooled odds ratio (OR) for subjective poor sleep in active IBD compared to remission of 3.04 (95% CI 2.41–3.83). Including only studies with objective sleep measures (5 studies), sleep efficiency was lower in those self-reporting active IBD and time awake post sleep onset was higher in those with active IBD. Objective IBD activity was associated with subjective poor sleep (4 studies), with pooled OR of 6.64 95% CI (3.02 – 14.59). Insufficient data was available to consider objective IBD activity and objective sleep quality. Conclusion: IBD activity is associated with poor sleep using subjective and objective measures of sleep quality. This poor sleep manifests as decreased sleep efficiency and increased number of waking episodes post sleep onset. The relationship between objective IBD activity and sleep requires further investigation.